The effects of absorptive and joint learning on the instability of international joint ventures in emerging economies - Fang, Eric; Zou, Shaoming (Journal of International Business Studies, 2010)
The objective of this study is to advance a theoretical framework pertaining to how interpartner learning in international joint ventures (IJV) may affect IJV instability in emerging economies. The proposed framework expands the interpartner learning theory of IJV instability in the current literature, which is focused on absorptive learning of IJV partners, by incorporating IJV partners’ joint learning. Using longitudinal dyadic data from IJVs in China, we found that local and foreign IJV parties’ absorptive learning capacity decreases one party's dependence on the other, while joint learning capacity in IJV increases both parties’ dependence on each other. In addition, an IJV partner's absorptive learning capacity positively moderates the effect of joint learning capacity on its dependence on another partner. These findings lend support to the expanded interpartner learning perspective of IJV instability, and have important theoretical and managerial implications for IJVs in emerging economies. The results underscore the importance of the IJV actively developing organizational rules, procedures, and structures to create and embed new knowledge in order to maintain the stability of the IJV. Finally, we found that IJV partners’ dependence asymmetry increases IJV instability, whereas their total dependence decreases IJV instability.